The meaning of Time magazine’s sign representation of visuals of 9/11: - Marla Koonin; Andrea Crysta (Communicare)
Baudrillard’s concepts of simulacra, simulation and hyperreality were assessed in relation to dominant themes and subthemes contained in the photographic images of Time magazine’s 9/11 special edition by means of a qualitative thematic content analysis. This event was selected based both on its becoming an ‘absolute event’ and on the resultant representation of said events via images. As such, visuals, because they contextually reflect a situation, play a powerful role in the representation of major world events. This is particularly true of photographs.